At the Earth's Core - Burroughs, Edgar Rice, 1875-1950 (Salt Lake City, UT : Project Gutenberg, 1994)
"At the Earth's Core" by Edgar Rice Burroughs is a fantasy novel written in 1914. When mining heir David Innes and inventor Abner Perry test an experimental drilling machine, they accidentally burrow 500 miles into Earth's crust and discover Pellucidar$1 (Ba hollow world within our planet. This prehistoric land is populated by ancient creatures and dominated by the intelligent but cruel Mahars, who enslave primitive humans. Innes must navigate strange customs, win the heart of Dian the Beautiful, and lead a human revolt against their reptilian overlords. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/At_the_Earth%27s_Core_(novel)
Pellucidar
Release date is 1994-04-01
Judith Boss
Keywords: Science fiction; Fantasy fiction; Adventure stories; Earth (Planet) -- Core -- Fiction